A Review Paper on Identification of Different Types of Indian Luxury Customers in the Apparel Sector with respect to Consumer Behaviour. - Gupta, Sheena; Banerjee, Dr. Sougata (IJRDO - Journal of Business Management, 2019)
India is on the fast-track to become one of the biggest luxury markets in the world. A lot of global luxury brands have entered India in the last 15 years. India is a large country with a lot of diversity. To distinguish themselves in the ever-expanding luxury customer base, luxury brands need to apply branding strategies specific to the Indian luxury consumer. A luxury brand cannot sustain itself by just applying its global, culture-neutral brand strategies in India. Thus, knowing, differentiating and segregating its consumer base becomes an important exercise for the brands to have successful marketing campaigns. This paper reviews the various consumer luxury segments studied and discovered across the globe and especially in India. The paper also discusses the various marketing strategies adopted by the luxury companies in India.